2020
DOI: 10.18231/2394-5478.2018.0094
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of mobile phones of healthcare workers at a tertiary care hospital

Abstract: Introduction: Mobile phones are used extensively by the healthcare workers who are completely unaware of the microbial load they carry. There are no guidelines on the cleanliness of these mobile phones which makes them an important source of hospital acquired infections among the patients in the hospital. Objectives: This study was conducted to determine the extent of bacterial colonisation of mobile phones from health care workers and elucidate its antibiotic sensitivity pattern. Settings and Design: The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
1
2
1
Order By: Relevance
“…As shown in Table 4, our antimicrobial susceptibility results indicate that all S. aureus isolates were resistant to methicillin and ceftazidine (100%). In the present study, the results demonstrated the sensitivity of isolates to penicillin, although this result does not agree with most studies that report the resistance of S. aureus to penicillin (Banawas, 2018;Siddiqui et al, 2018). This finding allows reusing penicillin as it has the advantage of being highly successful for prophylaxis and treatment.…”
Section: Antimicrobial Susceptibility Of S Aureus Isolatescontrasting
confidence: 94%
See 3 more Smart Citations
“…As shown in Table 4, our antimicrobial susceptibility results indicate that all S. aureus isolates were resistant to methicillin and ceftazidine (100%). In the present study, the results demonstrated the sensitivity of isolates to penicillin, although this result does not agree with most studies that report the resistance of S. aureus to penicillin (Banawas, 2018;Siddiqui et al, 2018). This finding allows reusing penicillin as it has the advantage of being highly successful for prophylaxis and treatment.…”
Section: Antimicrobial Susceptibility Of S Aureus Isolatescontrasting
confidence: 94%
“…In this study, all S. aureus isolates were sensitive to vancomycin, which is considered the last resort and line of antibiotics in humans. This finding agrees with the results obtained by Banawas et al (2018) and Siddiqui et al (2018). All isolates resistant to methicillin based on an insensitivity test suggest the presence of mecA gene, named MRSA (Geo et al, 2007).…”
Section: Antimicrobial Susceptibility Of S Aureus Isolatessupporting
confidence: 88%
See 2 more Smart Citations
“…Adapun hasil yang diperoleh dapat dilihat pada Tabel 1. (Kotgire et al, 2020) Untuk pencegahan infeksi adalah meminimalkan resiko kontaminasi pada handphone.…”
Section: Hasil Dan Pembahasanunclassified